2020
DOI: 10.4103/jfmpc.jfmpc_142_20
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome among southern region orthopedic surgeons, Saudi Arabia

Abstract: Background: Burnout is known as result of long term exposing to stress. There are some factors that may cause stress in physicians: nature of work, their training, their public image, their families and themselves. The person who has burnout syndrome (BOS) seems like to have tiredness, low energy, nervousness, and mentally unstable. The aim of the study is to assess the pattern and magnitude of burnout among orthopedic surgeons in southern region, Saudi Arabia. Methodology: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Several studies of burnout among physicians have been conducted in the Middle Eastern region (2,6,7,10,14). A recent review of seven studies in Arab countries assessed the prevalence of burnout among physicians reported ranges of burnout from 12.6% in Qatar up to 70% in Saudi Arabia (6).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of burnout among physicians have been conducted in the Middle Eastern region (2,6,7,10,14). A recent review of seven studies in Arab countries assessed the prevalence of burnout among physicians reported ranges of burnout from 12.6% in Qatar up to 70% in Saudi Arabia (6).…”
Section: Introductionmentioning
confidence: 99%
“…Included studies comprised quantitative research designs (n=26)[24,25,67,68, 69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90], qualitative research designs (n=9)[91, 92, 93, 94, 95, 96, 97, 98,99] and mixed research designs (n=2)[100, 101]. A total of 18,518 healthcare practitioners were included.…”
mentioning
confidence: 99%